An Analysis Of Ethical Education In Imam Al-Ghazali's Bidayatul Hidayah - Arifin, Zainal; Mubtadik, Mohamad Ayyub; Nurdalila, Umi Suciati (STAI Miftahul Ula Nganjuk, 2023)
Education is a conscious and planned effort to create an environment and active learning processes aimed at developing individual potential, encompassing spiritual and religious strength, self-control, personality, intelligence, noble character, and the skills needed by individuals, society, religion, the nation, and the state. In the modern era, many individuals focus solely on intellectual development, often neglecting the essential moral and ethical education that shapes societal attitudes towards education. This study examines the ethical education presented in the Bidayatul Hidayah, a classical Islamic text by Imam Al-Ghazali, which is expected to significantly support the 2013 Curriculum in fostering a generation with the desired Islamic educational characteristics. The research problem centers on identifying the forms of ethical education for teachers and students as outlined in Bidayatul Hidayah by Hujjatul Islam Imam Al-Ghazali. The aim of this research is to explore and understand the various aspects of moral education contained in this text. The study employs a library research methodology, collecting both primary and secondary data through document analysis. Data analysis is conducted using content analysis to ensure the validity of the findings through rigorous examination. The analysis reveals that Bidayatul Hidayah addresses a wide range of moral issues, including daily conduct, social ethics, teacher-student interactions, and the expected decorum of students when interacting with teachers.